Design Automation of Cyber-Physical Systems - Al Faruque, Mohammad Abdullah; Canedo, Arquimedes (Springer International Publishing : Imprint: Springer, 2019)
This book presents the state-of-the-art and breakthrough innovations in design automation for cyber-physical systems.The authors discuss various aspects of cyber-physical systems design, including modeling, co-design, optimization, tools, formal methods, validation, verification, and case studies. Coverage includes a survey of the various existing cyber-physical systems functional design methodologies and related tools will provide the reader unique insights into the conceptual design of cyber-physical systems. Provides a single-source reference on design automation of cyber-physical systems; Serves as a practical guide to managing complexity during the CPS development process with design automation tools and methodologies; Discusses modeling cyber-physical systems at various abstraction levels; Includes coverage of high-level synthesis for cyber-physical systems; Discusses design for performance/energy-efficiency/security, as well as various tools for validation and verification; Includes case studies in manufacturing and critical infrastructure systems.